Faktor Yang Berhubungan Dengan Pemanfaatan Pos Pembinaan Terpadu Lanjut Usia Di Wilayah Kerja Puskesmas Situmeang Habinsaran - Agustina, Winda (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2020)
Backgorund: Based on the 2013 National Development Planning Agency projection, the population of Indonesia in 2018 will reach 265 million. The number consisted of 133.17 million men and 131.88 million people. The number of elderly population reaches 60.8 million people or 22.9% of the total population and has increased 3 times compared to 2010. Metods: was analytical research with the correlation study research design using Chi-square data analysis of 0.05. The data was collected through questionnaires with a population of 552 and a total sample of 85 respondents at Working Area of ​​Situmeang Habinsaran Health Center in 2019. Result: Based on statistical tests using the chi-square test, the probability obtained (A symp Sig) knowledge was .000, Attitude .000, Family Support .000 was smaller than the confidence level of .05, the role of health workers was .088 greater than the confidence level> .05. Conclusion: of this study shows that there is a relationship of knowledge with the use of elderly Integrated Coaching Posts, there is a relationship between attitude and the use of elderly Integrated Coaching Posts, there is no relationship between the role of health workers with the use of elderly Integrated Coaching Posts, and there is a relationship of family support with the use of elderly Integrated Coaching Posts in the Working Area of ​​Situmeang Habinsaran Health Center.